Empowering Health Cadres Regarding the Smart Community Movement Using Medicine (Gema Cermat) As an Effort To Optimize Health Services in the Community: Pemberdayaan Kader Kesehatan Tentang Gerakan Masyarakat Cerdas Menggunakan Obat (Gema Cermat) Sebagai Upaya Optimalisasi Pelayanan Kesehatan di Masyarakat - Rambe, Robiatun; Virnoldi, Ukti; Hura, Arlitus; Taufik Daniel Hasibuan, Muhammad; Lusia Simatupang, Lenny; Yahya Gulo, Trifani (Universitas Haji Sumatera Utara, 2025)
In society, excessive use of drugs often occurs without a doctor's prescription and does not comply with the indications, dosage, technique, and duration of use, all of which can have a negative impact on health. Health cadres play an important role in inviting the community to come to health services, supporting medical personnel at integrated health posts, and helping the community access health information. This activity aims to improve cadres' knowledge and skills regarding drug use as well as skills in conveying information to the community. Implementation activities consist of several stages, namely: 1) Preparation, 2) Planning, and 3) Activities, Monitoring and Evaluation. The results of the activity showed that there was an increase in cadres' knowledge and skills regarding drug use as well as skills in conveying information in the community. It is hoped that health officers in the work area of the community health center can provide training and update information about health to cadres in order to create intelligent cadres, healthy communities and an advanced Indonesia.